2001
DOI: 10.1074/jbc.m101277200
|View full text |Cite
|
Sign up to set email alerts
|

A CalDAG-GEFI/Rap1/B-Raf Cassette Couples M1Muscarinic Acetylcholine Receptors to the Activation of ERK1/2

Abstract: In this study we examine signaling pathways linking the M 1 subtype of muscarinic acetylcholine receptor (M 1 mAChR) to activation of extracellular signal-regulated kinases (ERK) 1 and 2 in neuronal PC12D cells. We first show that activation of ERK1/2 by the M 1 mAChR agonist carbachol takes place primarily via a Ras-independent pathway that depends largely upon Rap1, another small GTP-binding protein in the Ras family. Rap1 in turn activates B-Raf, an upstream activator of ERK1/2. Consistent with these result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 92 publications
(142 reference statements)
3
48
1
1
Order By: Relevance
“…Rap activation is important for lymphocyte migration in vivo (53,54). The Rap-dependent signaling pathway activated by Epac is known to be cell-specific (55,56), and there is evidence for Rap-mediated action of Epac to stimulate mitogen-activated protein kinases (p38, extracellular signal-regulated kinase 1/2) in neurons, endocrine cells, and T-cells (57)(58)(59). Rap1 was reported to be activated by PKA through the phosphorylation of Rap1GAP (60), consistent with our finding that treatment of LAK cells with IL-8 or PKA activator did not show Rap1 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Rap activation is important for lymphocyte migration in vivo (53,54). The Rap-dependent signaling pathway activated by Epac is known to be cell-specific (55,56), and there is evidence for Rap-mediated action of Epac to stimulate mitogen-activated protein kinases (p38, extracellular signal-regulated kinase 1/2) in neurons, endocrine cells, and T-cells (57)(58)(59). Rap1 was reported to be activated by PKA through the phosphorylation of Rap1GAP (60), consistent with our finding that treatment of LAK cells with IL-8 or PKA activator did not show Rap1 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…In HEK293 cells, a 1 -adrenergic receptor-mediated activation of ERK1/2 appears to involve PKC-as well as Ca 2 þ -mediated pathways (Della Rocca et al, 1997). In addition to these typical Ga q -mediated pathways, it has also been shown that Ga q can activate ERK through a novel mechanism involving a DAG-as well as Ca 2 þ -dependent Rap-1-GEF (Guo et al, 2001). Using a variant of PC12 cells, PC12D, it has been shown that m 1 -muscarinic receptor stimulation of ERK1/2 modules is independent of Ras but dependent on Ga q -stimulated PLCb.…”
Section: G Q Stimulation Of Erk1/2mentioning
confidence: 99%
“…In support of this hypothesis, other GPCRs have also been shown to regulate ERK1/2 activity via B-Raf and Rap1. For example, the adenosine receptor (A 2A ), the prototypical ␤ 2 -adrenergic receptor, and the M 1 muscarinic receptor have all been found to stimulate ERK1/2 via Rap1 and B-Raf in CHO, HEK, and PC12 cells, respectively (51)(52)(53). These cells all express the Raf isoform B-Raf and are therefore able to activate ERK1/2 via cAMP signaling.…”
Section: Gip Activates Erk Via Rap1 Independently Of G␤␥ and Src-mentioning
confidence: 99%